Establishment of an effective photobioreactor for growing microalgae: A review - Md Mirazul Islam; Hasibul Alam; Aishi Acharjee; Md Salatul Islam Mozumder (International Journal of Agricultural Research, Innovation and Technology, 2025)
The premise that microalgae could be used to produce landscapes of biofuel, nutrition, and bioremediation is gaining popularity. The four main factors influential to microalgae growth are light, CO2, nutrients, and process conditions-including temperature and pH. Compared to other open systems such as ponds, control and efficiency in flat plate and tubular type photobioreactors are much higher. A photobioreactor needs to be developed to enhance the mass transport, and light penetration, and to reduce contamination. Every kind of photobioreactor has its advantages and limitations in using the airlift, bubble column, and stirred tank. Thus, the use of hybrid bioreactors makes it possible to eliminate individual limitations. This review discusses and analyzes the features of photobioreactor systems, their drawbacks, and the progress achieved in the field of microalgae production. Int. J. Agril. Res. Innov. Tech. 14(2): 153-162, December 2024